Development An Intelligent Controller Of An Autonomous Mobile Robot - Wong, Hon Loon (UTeM, 2009)
This project is proposed to develop a tracking controller for the dynamic model of unicycle mobile robot by integrating a kinematics controller and a torque controller based on Fuzzy Logic Technique. The main objectives are to prove the mathematical model which represents the tracking controller of the mobile robot by using the control law and design an intelligent controller for a unicycle mobile robot. This project is divided into two parts. The first part is to develop and prove the mathematical model of a unicycle mobile robot in the form of equations by using Matlab. Then, controllability and stability of the kinematic model is shown from the errors whether the mobile robot velocities reach the given velocity inputs, and a fuzzy logic controller such that provided the required torques for the actual mobile robot. Meanwhile, the second part is to develop the tracking controller by using fuzzy logic controller. Computer simulations are presented confirming the performance of the tracking controller and its application to different navigation problems.